Protection of the Child as Non-Therapeutic Research Subject - Benyamin Lumenta (Paediatrica Indonesiana, 1989)
As a developing country, the more research will be performed, scientific as well as industrial, the more will be emphasized on the rights of the individual, particularly of the research subject. This paper is a literature review on medical ethics pertaining to the protection of the rights of children as research subject in advanced communities. Much can be expected from it for the benefit of moral and ethical development in our eastern paternalistic dominated research performance. It will show the historical development of medical ethical analysis and its role in the decision making process at all levels of biomedical research involving children as incompetent patients because of age, or as healthy people under the competent or consent age. The psycho-social evaluation of the child and the conflicting views of biomedical research of the child has been discussed widely in the literature. The last two decades experienced an abundance in studies on child education, establishing ethics pertaining the child's rights and other philosophies. Nevertheless, there still seems to be no apparent consensus pertaining what good life is to the child and yet no uniformity as to the evaluation concerning development of a good life for the child. Besides, biomedical research encounters conflicting public opinions, as Curran (1977) observed three basic conflicting views, i.e. 1st, the protection of the research subject, 2nd, the societal needs for research outcomes, and 3rd, the promotion and encouragement of medical researchers.